Regional SME Support Instruments on the Example of Selected EU Countries - Based on Research Conducted in the Kuyavian-Pomeranian Voivodship in Poland - Zbigniew GRZYMAŁA (Communications of International Proceedings, 2021)
Economic development is created on three basic levels: central, for which governments are responsible, regional, where responsibility rests with the regional authorities, and local, which may be inspired by communes. Governments set general priorities and directions in their planning documents in the first place. They can establish central institutions supporting the financing of enterprises. However, in many EU havens a central role is assigned to regional instruments. The aim of the article is to present the regional instruments of economic development developed as part of the research carried out by the Kujawsko-Pomorskie Voivodship, the Warsaw School of Economics and the Nicolaus Copernicus University (Gospostrateg Programme, 2020). These instruments were presented against the background of similar instruments in selected European countries. Most often at the regional level, strategies for the development of regions and individual industries in these regions, including innovative industries, are created. In the case of the Kujawsko-Pomorskie Voivodship, it was decided, inter alia, to develop an economic development program, which focused on projects favouring regional entrepreneurship. Regions, next to financial support institutions, can also better look at economic development indicators in the region and thus inform regional authorities and entrepreneurs about development trends, threats or opportunities. Such instruments are more and more often the so-called regional economic observatories.
Keywords: Economic Development; Region; SME; Local Government.